Perbandingan Kinerja Keuangan PT. Telkom Indonesia Tbk Dan PT. Indosat Tbk Sebelum dan Sesudah Covid 19 - Edi Nurgiyantoro; Sri Hemuningsih (Universitas Batanghari, 2023)
A company's financial performance is crucial and valuable because it reflects how effectively it can manage its financial resources to support management in their decision-making. Financial performance measurement is frequently used as a foundation for evaluating success and understanding a company's strengths and weaknesses so that management can assess, choose, and implement the best course of action for the company's survival, particularly during the Covid-19 pandemic, which has a significant negative impact on human life throughout the world, including in Indonesia. The goal of this study is to compare the financial performance of PT. Telkom Indonesia Tbk and PT. Indosat Tbk before and after the Covid-19 pandemic from 2017 to 2021 using quantitative data research methods and a descriptive approach. The data used in this study is only secondary data in the form of annual financial statements that were obtained from the website of the Indonesia Stock Exchange (www.idx.co.id) and calculated using financial ratio analysis. The findings indicated that PT Telekom Tbk had better average values for the following ratios than PT Indosat Tbk: current ratio (CR), debt to asset ratio (DAR), debt to equity ratio (DER), total asset turnover (TATO), net profit margin (NPM), return on assets (ROA), and return on equity (ROE).